Pendidikan dan Gender : Studi Tentang Bias Gender dalam Buku Pelajaran Agama Islam - Asniar Tanjung (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to identify and analyze forms of gender bias found in Islamic Religious Education (PAI) textbooks at the Senior High School (SMA) level. Using a qualitative approach with content analysis methods, grounded in a critical paradigm and gender perspective, this research found that gender representation in several teaching materials remains unequal. Gender bias in the textbooks is manifested through narratives that position men as dominant in the public sphere, while women are confined to domestic roles. The analyzed materials include topics such as pilgrimage requirements, covering the body and dressing, visiting graves, marriage guardians and witnesses, and family leadership. In these narratives, women are often portrayed as weak, in need of protection, or limited in their roles. This indicates that PAI textbooks continue to reproduce patriarchal values that may reinforce gender-based social inequalities in educational settings. The study recommends that teaching materials be revised to be more inclusive and aligned with gender equality principles as mandated by national education regulations. Thus, education can serve as a fair and equitable instrument for all students, regardless of gender.